Разработка шихты на основе порошковой системы TiNi, Ti, Ni для создания методом реакционно-диффузионного спекания и электронно-пучковой обработки пористых покрытий - Волочаев, Михаил Николаевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The work is devoted to the development of the charge based on the powder system TINI, TI, N1 for creating porous coatings by the method o f reaction-diffusion sintering and electron-beam processing. Several compositions [(TiNi-5Ti-0.5Ni):(Ti+Ni)J in various proportions have been obtained, porous materials based on them have been studied, and suitable thermal and temporal modes of reaction-diffusion sintering in an electric vacuum furnace have been determined. Due to the introduction of exothermic additives of Ti and Ni powders in various proportions to the calcium hydride TiNi powder, a regular porous structure is maintained, the holding temperature is reduced, and martensitic transformations are preserved.